Analysis of the Effect of Population Growth on Settlement Development in Itawaka Village, East Saparua District - Sakallessy, Gracellia; Lasaiba, Mohammad Amin (GEOFORUM, 2025)
Population growth is a crucial factor influencing the development of settlements, particularly in rural areas. This study analyzes the impact of population growth on settlement development in Itawaka Village, East Saparua District, from 2014 to 2023. The research employs a quantitative approach using simple linear regression analysis to measure the extent to which population changes affect settlement expansion and infrastructure development. The results indicate that the highest population was recorded in 2018 at 2,099 inhabitants, followed by a significant decline, reaching 1,882 in 2023. The analysis reveals a strong correlation between population growth and settlement expansion, with an R-square value of 0.699, meaning that 69.9% of settlement development variations can be explained by demographic changes. The findings highlight the need for sustainable settlement planning to address population fluctuations and ensure balanced infrastructure development. This study contributes to understanding the relationship between demographic trends and spatial planning in coastal rural areas, providing insights for policymakers in formulating sustainable settlement strategies.